Complete convergence for weighted sums of i.i.d. random variables with applications in regression estimation and EV model. Issue 7 (3rd April 2017) - Chen, Pingyan; Kong, Ningning; Sung, Soo Hak
ABSTRACT: In this paper, we obtain complete convergence results for Stout type weighted sums of i.i.d. random variables. A strong law for weighted sums of i.i.d. random variables is also obtained. As the applications of the strong law, the strong consistency and rate of the nonparametric regression estimations and the rates of the strong consistency of LS estimators for the unknown parameters of the simple linear errors in variables (EV) model are given.